Silver nano platelet films on soft micro grating surface. Issue 1 (7th January 2019) - Mehdi, Murtuza; Chandio, Alidad; Akhtar, Maaz; Khan, Zaibullah; Zaman, Ahsan; Muhammad, Adeel
Abstract : Purpose: Polymer substrates with micron size roughness features have been found to play an important role in the mechanical performance of thin functional films which are used extensively in stretchable and flexible micro electromechanical systems. The purpose of this study is to report the stretchability and flexibility limits of micro size silver nano platelet films on a soft polymer substrate having two different orientations of micro grating with respect to the applied load. Design/methodology/approach: Parallel and perpendicular micro gratings on the surface of a soft polymer substrate polydimethylsiloxane were patterned using a carefully machined master aluminum block and thin aluminum foils. Silver nano platelet-based films were rod coated on the substrate surface containing the micro gratings. These films were dried in ambient air and were tested for their stretchability and flexibility limits using homemade tools. Finite element modeling has also been performed and was found to support the experimental observations. Findings: Experiments indicate that stretchability of silver nano platelet-based thin films tends to increase when the grating orientation remains parallel to the axis of the applied load, while its flexibility improves when the orientation becomes perpendicular to the loading axis. Originality/value: The effect of grating orientation with respect to the applied load was investigated. The experiments show that micro grating roughness features are capable of enhancing the mechanical performance of nano platelet-based silver films on a soft polymer substrate and can be used in various stretchable and flexible micro electro mechanical device applications.